Pregnane X receptor reduces particulate matter-induced type 17 inflammation in atopic dermatitis - Lee, Ji Su; Lee, Youngae; Jang, Sunhyae; Oh, Jang-Hee; Lee, Dong Hun; Cho, Soyun (Frontiers in Immunology, 2024)
Background: Epidemiological evidence suggests that particulate matter (PM) exposure can trigger or worsen atopic dermatitis (AD); however, the underlying mechanisms remain unclear. Recently, pregnane X receptor (PXR), a xenobiotic receptor, was reported to be related to skin inflammation in AD. Objectives: This study aimed to explore the effects of PM on AD and investigate the role of PXR in PM-exposed AD. Methods: In vivo and in vitro AD-like models were employed, using BALB/c mice, immortalized human keratinocytes (HaCaT), and mouse CD4+ T cells. Results: Topical application of PM significantly increased dermatitis score and skin thickness in AD-like mice. PM treatment increased the mRNA and protein levels of type 17 inflammatory mediators, including interleukin (IL)-17A, IL-23A, IL-1β, and IL-6, in AD-like mice and human keratinocytes. PM also activated PXR signaling, and PXR knockdown exacerbated PM-induced type 17 inflammation in human keratinocytes and mouse CD4+ T cells. In contrast, PXR activation by rifampicin (a human PXR agonist) reduced PM-induced type 17 inflammation. Mechanistically, PXR activation led to a pronounced inhibition of the nuclear factor kappa B (NF-κB) pathway. Conclusion: In summary, PM exposure induces type 17 inflammation and PXR activation in AD. PXR activation reduces PM-induced type 17 inflammation by suppressing the NF-κB signaling pathway. Thus, PXR represents a promising therapeutic target for controlling the PM-induced AD aggravation.